2021
DOI: 10.1108/ijlm-06-2020-0237
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging big data analytics capabilities in making reverse logistics decisions and improving remanufacturing performance

Abstract: PurposeThe study investigated the effect of big data analytics capabilities (BDACs) on reverse logistics (strategic and tactical) decisions and finally on remanufacturing performance.Design/methodology/approachThe primary data were collected using a structured questionnaire and an online survey sent to South African manufacturing companies. The data were analysed using partial least squares based structural equation modelling (PLS–SEM) based WarpPLS 6.0 software.FindingsThe results indicate that data generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 94 publications
(127 reference statements)
1
13
0
Order By: Relevance
“…Our study revealed that the BDCC of BDAC both directly affects innovative performance and mediates the relationship between BDU and IOP. These findings support previous studies (Bag et al, 2021;Buhalis & Volchek, 2021;Ciampi et al, 2021;Côrte-Real et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed that the BDCC of BDAC both directly affects innovative performance and mediates the relationship between BDU and IOP. These findings support previous studies (Bag et al, 2021;Buhalis & Volchek, 2021;Ciampi et al, 2021;Côrte-Real et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…BDACs provide a competitive edge (Bag et al, 2021; Gupta et al, 2020), including in international tourism markets (Aakash & Gupta Aggarwal, 2020; Yasar & Demir, 2019). As part of BDAC, big data can be collected to identify changing customer trends, employee expectations, the sustainability of relations with stakeholders and the hotel's social image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Big data also help decision-making accuracy within an organization, 6 the fourth paradigm of science, 7 maximizing innovation performance, 8 and reducing expenses. 9…”
Section: Introductionmentioning
confidence: 99%
“…5 Big data also help decision-making accuracy within an organization, 6 the fourth paradigm of science, 7 maximizing innovation performance, 8 and reducing expenses. 9 Some scholars argue that investing in BDAC is a fallacy since by using this talent, a company's innovation performance has improved, even if BDAC has changed from a more traditional organization to one that does innovation work. 10,11 Organizations are expected to use effective innovation technology to maintain adequate productivity levels in their environments.…”
Section: Introductionmentioning
confidence: 99%